Going beyond co-production: a public contributor led, local evaluation of the National Institute of Health and Social Care (NIHR) Research Champion role - Julie Hedayioglu; Frances Mossie; Carol Coleman (Research Involvement and Engagement)
Abstract Background The National Institute of Health and Social Care (NIHR) Research Champion (RC) role, has grown over the last few years. This public contributor role was designed to engage and involve patients and the public in health and care research within the NHS. Yet, there has been little focus on how it is working and experienced. Moreover, there is a lack of research that has been initiated, and/or led, by patients and the public. Aim To conduct a public contributor led evaluation to understand the experiences and perceived impact of the NIHR RC role that supports NHS research. Method A qualitative, formative evaluation using semi-structured interviews. Results Rich and detailed data was obtained from 11 RCs and 4 staff members with thematic analysis identifying four main themes: RC Activities, Recruitment and Background of RCs, their Support and Engagement, and the Impact of the RC role. Conclusions The RC role is highly valued by both staff and volunteers, and is versatile; it can be adapted to the needs of the research, volunteers, and hosting organisations. There are challenges in recruiting to the role but there are many positives to those that have taken it up. These include giving dedicated time, bringing valuable life experiences and professional skills, and being a meaningful activity for the RCs. Greater awareness and recognition of this role as a valuable resource is needed with more attention and investment required to staff supporting RCs.